Clinical Features of Pediatric Idiopathic Intracranial Hypertension and Applicability of New ICHD-3 Criteria - Moavero, Romina; Sforza, Giorgia; Papetti, Laura; Battan, Barbara; Tarantino, Samuela; Vigevano, Federico; Valeriani, Massimiliano (Frontiers in Neurology, 2018)
Idiopathic intracranial hypertension (IIH) is characterized by intracranial pressure >28 cmH2O in the absence of identifiable causes. Aim of this paper is to describe the clinical phenotype of pediatric IIH and to analyze the applicability of ICHD-3 criteria in comparison to the ICHD-2. We conducted a retrospective analysis of full clinical data of pediatric patients diagnosed with IIH between January 2007 and June 2018. Diagnostic evaluation included neuroimaging (all patients) and ultrasound-based optic nerve sheath diameter measurement (9 patients). Diagnosis of IIH was verified according to both ICHD-2 and ICHD-3 criteria for headache attributed to IIH, to verify the degree of concordance. We identified 41 subjects with suspected IIH; 14 were excluded due a diagnosis of secondary IH or lack of data. We therefore selected 27 subjects (age 4-15 years, mean 11). All patients presented with headache and bilateral papilloedema. Headache was daily in 22% cases, with diffuse gravative pain in 41%. In 4%, pain was exacerbated by cough, stress or tension. The most common presentation symptoms, in addition to headache, were blurred vision or diplopia (70%), vomiting (33%), and dizziness (15%). Twenty patients (74%) were obese. In 6 patients (22%) neuroimaging showed empty sella. Optic nerve sheath distension was detected in 6 out of 9 patients. Regarding the applicability of the ICHD-2 criteria, 18/27 (71%) patients have criterion A; 24/27 (89%) criterion B; 27/27 (100%) criterion C; 27/27 (100%) criterion D. When the ICHD-3 criteria were used, 27/27 (100%) fitted criterion A; 24/27 (89%) criterion B; 27/27 (100%) criterion C; and 27/27 (100%) criterion D. Our study suggests that, as compared with the ICHD-2, the new ICHD-3 criteria for headache attributed to IIH are better satisfied by pediatric patients with IIH. This is mainly due to the fact that qualitative headache characteristics are no longer considered in ICHD-3. Although the risk of under-rating the symptom of headache in IIH should not be disregarded, in pediatric population headache characteristics are usually less defined than in adults and obtaining a precise description of them is often very difficult.